Complex dynamics through fuzzy chains. - Bucolo, M. (IEEE Transactions on fuzzy systems)
This paper gives a new contribution to characterize a class of complex systems build as arrays of coupled fuzzy logic based chaotic oscillators and investigates their dynamical features. Different spatio-temporal dynamics have been reproduced using interconnected fuzzy chaotic cells in order to study the effects, due to the variation of some parameters and network topologies, in the collective behavior and to highlight the synchronization capability of the complex fuzzy systems under consideration. The synchronization characteristics have been focused by defining a behavioral index.